Can Online College Education Make Students Smarter and More Moral? A Preliminary Study of the Effects of Two Online College Course Assignments on Students’ Moral Competence - Klimenko, Marina A.; Surdel, Nicholas; Muir, Kathryn; Sofia, Fuaad (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2018)
Higher education institutions in the United States have historically been tasked with the responsibility of scaffolding the moral development of students. Although empirical evidence suggests that attending colleges and universities can foster students’ moral development and reasoning, the effect of online higher education remains mainly unknown. The current study has examined the effect of two online psychology courses, Developmental Psychology and Research Methods Lab, and their respective assignments on students’ moral competence. The findings revealed that students’ moral competence in both courses was improved; this improvement was partly attributed to online group discussions in the Developmental psychology course. No other assignments were found to be significant contributors of students’ moral competence. Limitations and implications of the findings were discussed.
Keywords: morality; higher Education; online Higher Education; moral Competence; moral Development